2014
DOI: 10.1071/is13017
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of two new species of freshwater crabs from the Seychelles based on molecular evidence (Potamoidea : Potamonautidae)

Abstract: Abstract. The Afrotropical freshwater crab genus Seychellum is endemic to the granitic Seychelles in the Indian Ocean (Mahé, Silhouette, Praslin, La Digue and Frégate). Here we describe two new cryptic species of Seychellum that represent two evolutionarily separate lineages of a previously monotypic genus. This raises to three the number of species of freshwater crabs known from Seychelles. Each species is endemic to either one island (Silhouette) or to a pair of islands (Mahé and Frégate, or Praslin and La D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a fine‐scale study of the burrowing freshwater crab Potamonautes calcaratus , restricted to ephemeral pans in the Kruger National Park, South Africa, Daniels et al (2002) reported moderate genetic structuring. In the Seychelles freshwater crab, Seychellum alluaudi , three distinct clades were observed that corresponded to different islands in the archipelago (Daniels, 2011) and were later described as three allospecies (Cumberlidge & Daniels, 2014). On Mahé Island alone, Seychellum mahefregate had an uncorrected sequence divergence value of 3.18%, and three distinct haplogroups were detected, coinciding with the central mountain ridges that are present on the island (Daniels, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a fine‐scale study of the burrowing freshwater crab Potamonautes calcaratus , restricted to ephemeral pans in the Kruger National Park, South Africa, Daniels et al (2002) reported moderate genetic structuring. In the Seychelles freshwater crab, Seychellum alluaudi , three distinct clades were observed that corresponded to different islands in the archipelago (Daniels, 2011) and were later described as three allospecies (Cumberlidge & Daniels, 2014). On Mahé Island alone, Seychellum mahefregate had an uncorrected sequence divergence value of 3.18%, and three distinct haplogroups were detected, coinciding with the central mountain ridges that are present on the island (Daniels, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a fine-scale study of the burrowing freshwater crab Potamonautes calcaratus, restricted to ephemeral pans in the Kruger National Park, South Africa, Daniels et al (2002) reported moderate genetic structuring. In the Seychelles freshwater crab, Seychellum alluaudi, three distinct clades were observed that corresponded to different islands in the archipelago (Daniels, 2011) and were later described as three allospecies (Cumberlidge & Daniels, 2014 . Assuming that the species is now known from two isolated centres of distribution in KwaZulu-Natal and the Eastern Cape, the question arises as to whether dispersal among the two provinces, as suggested by the microsatellite data and, in one example, based on the COI data, is likely.…”
Section: Spatial Distribution Of Potamonautes Lividusmentioning
confidence: 99%
See 1 more Smart Citation
“…is not phylogenetically determined and may well reflect habitat similarities and environmental drivers, given their current distributions. This may support the lack of distinctive species-specific characters that appears to be a widespread trend for African potamonautids ( Daniels et al 2003 , Jesse et al 2010 , Cumberlidge and Daniels 2014 , Phiri and Daniels 2014 , Phiri and Daniels 2016 ).…”
Section: Discussionmentioning
confidence: 77%
“…If all trogloplacines have abbreviated (or at least a semi-abbreviated) development and there are no free-swimming larvae, how did they disperse so widely? Despite hypotheses that primary freshwater crabs may have dispersed through Gondwanic connections (Ng et al 1995), the available evidence is that they are not old enough to have done so (see Daniels et al 2006; Cumberlidge et al 2008; Klaus et al 2009; Cumberlidge and Ng 2009; Daniels 2011; Cumberlidge and Daniels 2014); and as such, the disjunct distribution of A. insperatus sp. n. begs further studies.…”
Section: Systematicsmentioning
confidence: 99%